Ambulation recovery prediction after hip fracture surgery using the Hip Fracture Short-Term Ambulation Prediction tool - Nath Adulkasem; Pojchong Chotiyarnwong; Ekasame Vanitcharoenkul; Aasis Unnanuntana (Medical Journals Sweden, 2024)
Objective: To develop models for predicting postoperative ambulation recovery at 3 months following fragility hip fracture surgery. Design: Cross-sectional study. Subjects: Fragility hip fracture patients aged ≥ 50 years who underwent operative treatment and completed a 3-month follow-up. Methods: Potential predictors were collected from eligible patients, while ambulation at 3 months after injury was assessed using the modified functional ambulation classification. These factors were used to develop the Hip Fracture Short-Term Ambulation Prediction, consisting of 2 models: Model 1 for postoperative ambulation and Model 2 for preinjury status recovery. Results: Among the 275 patients, 55 (20.0%) achieved good ambulation, and 59 (21.5%) returned to their preinjury status at 3 months. Age, preinjury ambulatory status, and discharge ambulatory status were identified as significant predictors of 3-month postoperative ambulation. The tool presented (Models 1 and 2) showed strong performance (area under the curve of 0.86 and 0.85, respectively) and good internal validity. Conclusions: Age, preinjury ambulatory status, and discharge ambulatory status significantly predict postoperative ambulation and preinjury status recovery at 3 months after fragility hip fracture surgery. The tool presented may aid clinicians in identifying patients who could benefit from targeted rehabilitation interventions during this crucial period.